The universal Turing machine interpreter - Kurgaev, A.F.; Grygoryev, S.N. (Reports of the National Academy of Sciences of Ukraine, 2016)
Using an interpreter of the universal Turing machine as the example, it is shown that the NFK (normal forms of knowledge) meta-language expressiveness is sufficient for defining and solving any solvable problem, which proves the versatility of a computer, which realizes this language. In the process of substantiation of the versatility of the NFK meta-language, the formal text and graphical descriptions of an interpreter of the universal Turing machine are given.